Бухгалтерский учет, анализ и аудит: учебное пособие - Пономаренко П. Г. Павел Григорьевич; Медведев А. В. Александр Владимирович; Трофимова А. Н. Анна Николаевна; Затолгутская Н. Н.; Чмыхова Ж. М. (Минск, Вышэйшая школа, 2010)
Авт. указаны на обороте тит.